Desain Etnoparenting Berbasis Adat Alam Minangkabau untuk Character Build Anak Usia Dini di Era Digital: Minangkabau Nature-Based Ethnoparenting Design for Early Childhood Character Build in the Digital Age - LINA - AMELIA; Faizatul Faridy (Universitas Ngudi Waluyo, 2023)
Children are an investment in the future of a nation because children are the next generation of the nation. Alpha generation children have begun to thin out their character values. The digital era with all its conveniences gives rise to individualism, irritability, a lack of sharing, and even a lack of socialization, so the internalization of moral and social values ​​begins to wane. The first step that parents and families can take is to return to exploring the values ​​of each other's cultural wisdom to be used as a basis for parenting. The ethnoparenting design is extracted from the noble values ​​of Minangkabau traditional culture. This development produces products in the form of teaching videos and guidebooks for teachers and parents. Techniques for extracting the positive values ​​of Minangkabau natural culture with storytelling techniques with pictures or videos. There are 4 character values ​​explored in this study, namely the character of appreciating achievement extracted from the story of the origin of the Minangkabau name, the character of communication/friendship is extracted from the positive values ​​of kato mandaki, kato manurun and kato mandata, the value of independence and social care is extracted from the positive values ​​of Minangkabau natural customs stored from the rankings. In terms of children's acceptance of teaching materials, it can be illustrated from the results of trials at An-Nur Aceh Besar Kindergarten, from 30 children who watched teaching videos, 18 children (60%) were able to answer teacher questions from the one-time playing process and 23 children (76,6%) can answer the teacher's questions after playing the teaching video 2 times. This proves that children can understand the contents of the teaching videos. ABSTRAK Anak adalah investasi masa depan suatu bangsa karena anak adalah generasi penerus bangsa. Anak-anak generasi alpha sudah mulai menipis nilai-nilai karakternya. Era digital dengan segala kemudahannya memunculkan sifat individualisme, mudah marah, kurang mau berbagi bahkan kurang sosialisasi sehingga internalisasi nilai-nilai moral dan social mulai berkuang. Langkah awal yang bisa dilakukan orang tua dan keluarga adalah Kembali menggali nilai-nilai kearifan budaya masing-masing untuk dijadikan bahan pijakan dalam pengasuhan anak. Desain etnoparenting yang digali dari nilai-nilai luhur budaya adat minang kabau. pengembangan ini menghasilkan produk berupa video ajar dan buku panduan untuk guru dan orang tua. Teknik penggalian nilai positif budaya alam Minangkabau dengan Teknik story telling dengan gambar atau video. Nilai karakter yang digali dalam penelitian ini ada 4 yaitu karakter menghargai prestasi digali dari cerita asal usul nama Minangkabau, karakter komunikasi/ bersahabat digali dari nilai positif kato mandaki, kato manurun dan kato mandata, nilai kemandirian dan peduli social digali dari nilai postif adat alam Minangkabau yang tersimpan dari rangkiang. Dilihat dari segi penerimaan anak terhadap bahan ajar dapat digambarkan dari hasil uji coba di TK An-Nur Aceh Besar dari 30 anak yang menonton video ajar 18 anak (60%) dapat menjawab pertanyaan guru dari proses satu kali diputarkan dan 23 anak (76,6%) dapat menjawab pertanyaan guru setelah 2 kali diputarkan video ajar. Ini membuktikan isi video ajar dapat dipahami anak.